Statistical analyses of gender disparities in unpaid work in Georgia - Gelashvili, Simon; Okruashvili, Mariam (Edelweiss Applied Science and Technology, 2024)
Using data from the Labour Force Survey (LFS) with a quarterly sample size of 6,400 households and the Georgia Time Use Survey (GTUS) covering 3,680 households nationwide, this article investigates gender disparities in unpaid work in Georgia and their impact on individual welfare. Employing international methodologies, we calculated new statistical indicators and refined existing ones, including the improvement of Sustainable Development Goal indicator 5.4.1 (SDG 5.4.1). Regression analysis identified education level as a significant factor influencing unpaid work. Our findings underscore significant gender disparities in unpaid work, leading to heightened workloads and temporary poverty for women. These disparities persist across various demographic factors. This research contributes to understanding the dynamics of unpaid work and its implications for gender equality and welfare.